Effective presentation skills - Mandel, Steve (Crisp Pub. Menlo ParkUS, 1993)
Provides a useful definition of a presentation. Seeks to help readers to organize, plan and deliver effective presentations. Topics include: developing and using visual aids; dealing with anxiety; and question and answer techniques.